Optimización del secado de rodajas de mango variedad Haden (Mangífera indica L.) por conbinación de microondas y aire caliente - Barranzuela Mendocilla, Anthony William (2014)
In the present work entitled "Optimizing drying Variety Haden mango slices (Mangífera indica L.) by combining microwave and hot air" the effect of microwave power and hot air temperature on moisture and color variation of the mango slices were studied. Were considered the residence time, thickness of the handle. It was a full 2k factorial planning, including four axial points and an arbitrary number of central points (3 in this work), which gave us the total number of 11 trials, which allowed us to obtain the models that define the behavior of variables responses to moisture and color variation. The models were highly significant at p <0.05 and for presenting a high coefficient of determination R2 was possible to construct the response surfaces. It was used a Central Composite Rotational Design to evaluate the optimum moisture areas and variation of color cause, always seeking to optimize humidity according to the specifications and reduce color variation. According to this design, the optimum moisture content between 9-13% less color variation is achieved when the hot air temperature is between 60 ° C and 70 ° C and combined with microwave power between 500 and 700 Watts.